(untitled) (Medical Forum Monthly, 2024)
Objectives: To find out the magnitude, manner and modalities of unnatural deaths among all cases brought to the Forensic Medicine Department (PMC) Faisalabad for post mortem examination. Study Design: Retrospective study. Place and Duration of Study: The study was conducted in the Department of Forensic Medicine, Punjab Medical College Faisalabad from 1st January, 2012 to 31st December, 2012. Materials and Methods: Study material has been collected from mortuary of (PMC) Faisalabad including police inquest reports, postmortem reports and hospital record / treatment history of the victims. A total of 397 cases of Medico legal deaths were brought for postmortem examination in the Department of Forensic Medicine, Punjab Medical College Faisalabad during one year study period. All these cases were grouped according to age, gender, manners and modalities of medico legal / unnatural deaths. The data collected, & analyzed. Results: The commonest manner of death in overall age groups was homicide followed by accident, suicide & natural deaths, whereas; 59 cases remained undetermined. Among 228 homicidal deaths, Firearms were the predominant weapons of infliction (70.17%). A total of 64 (85.33%) persons lost their lives in Road Traffic Accidents (RTA) among 75 accidental deaths. Out of total 397 cases, Males were (74.82%) and females (25.18%). The age group most commonly involved was 20-29 years (29.97%) followed by 30-39 years (21.41%) & 40-49 years (15.61%), whereas; the victims belonging to age group of 10-19 years contributed for (12.09%). Conclusion: Our study concludes that Homicide was the most dominant manner of death among the unnatural deaths. Fatalities caused by Firearms were the commonest form of homicide; Road Traffic Accident was the commonest modality among accidental deaths whereas; the suicide was found as rare manner of death.